Bilateral Signet-ring Stromal Tumor of the Ovary: A Case Report With Next-generation Sequencing Analysis and FOXL2 Mutation Testing. (March 2020) - Chen, Po-Han; Hui, Pei; Buza, Natalia
Abstract : Signet-ring stromal tumor (SRST) is a rare benign stromal neoplasm of the ovary with only a handful of cases reported in the literature. To date, all but one reported cases have been unilateral, and the pathogenesis and underlying genetic abnormalities of this entity are not well characterized. Here we report a case of a 70-yr-old woman with bilateral ovarian SRST, clinically presenting with abdominal distention and rectal bleeding, and bilateral ovarian masses on imaging studies. Total hysterectomy and bilateral salpingo-oophorectomy were performed, revealing bilateral solid ovarian tumors with characteristic signet-ring cell morphology. The immunohistochemical profile—positive steroidogenic factor 1, calretinin, and smooth muscle actin, and negative epithelial membrane antigen—supported the diagnosis of SRST. CTNNB1 mutation and abnormal nuclear beta-catenin expression have recently been reported in 2 SRSTs. However, we did not identify any mutations in 54 oncogenes and tumor suppressor genes (including CTNNB1 ) by next-generation sequencing analysis, and PCR Sanger sequencing did not reveal FOXL2 C134W mutation, suggesting the possibility of heterogenous pathogenesis of these tumors.